Effect of neuromuscular electrical stimulation on facial muscle strength and oral function in stroke patients with facial palsy - Choi, Jong-Bae (Journal of Physical Therapy Science, 2016)
[Purpose] The aim of this study was to investigate the effect of neuromuscular electrical stimulation on facial muscle strength and oral function in stroke patients with facial palsy. [Subjects and Methods] Nine subjects received the electrical stimulation and traditional dysphagia therapy. Electrical stimulation was applied to stimulate each subject’s facial muscles 30 minutes a day, 5 days a week, for 4 weeks. [Results] Subjects showed significant improvement in cheek and lip strength and oral function after the intervention. [Conclusion] This study demonstrates that electrical stimulation improves facial muscle strength and oral function in stroke patients with dysphagia.